Comparative analysis of powertrain optimization for Small electric vehicle based on range and weight for Retro-fitment. (2022) - Vignesh, S.; Bhateshvar, Yogesh Krishan; Agrewale, Mohammad Rafiq B.; Vora, K.C.
Abstract: Range anxiety starts from the battery pack in an electric vehicle. It is one of the areas, where plenty of research is in progress on the development of battery packs. In Small Electric Vehicle (SEV), especially with retro fitment scenario, the floor-mounted battery pack is difficult. This paper focuses on proposing the battery pack concepts for SEV to maximize the range and weight distribution. In this paper, SEV is proposed for urban mobility requirements and the battery pack is mounted on the front and rear hood, which is based on the volume available for mounting in the SEV. Motor for SEV is taken from literature and the powertrain is optimized based on weight and range of SEV. The battery packs considered in this paper are Lead-acid, Nickel Metal Hydride, Lithium Polymer, Lithium-Sulfur, and Zinc-air. Range estimation is done for all the battery packs. Based on the projected battery pack weight at the front and rear hood, Weight distribution is given higher importance in the optimization of battery packs apart from range including its mounting. The Weight distribution is analyzed by keeping the Body in White (BIW) of SEV as constant and different variants of electric powertrains proposed.